Responsibility in Public Services at The Tirta Darma Ayu Regional Public Drinking Water Company, Sindang Service Branch, Indramayu Regency - Putra Kurniawan; Hery Nariyah; Nursahidin (Rescollacom (Research Collaborations Community), 2026)
Abstract Service responsiveness is a critical dimension of public service quality, particularly in essential sectors such as clean water provision, where service disruptions directly affect community welfare. This study aims to analyze the responsiveness of public service delivery in handling customer complaints at the Sindang Service Branch of the Tirta Darma Ayu Regional Public Drinking Water Company (PERUMDAM) in Indramayu Regency. The research focuses on identifying the level of responsiveness, the constraints faced in service implementation, and potential strategies to improve complaint handling performance. This study employs a qualitative descriptive approach. Data were collected through observations, in-depth interviews, and document analysis involving key informants, including managerial staff, service officers, technical personnel, and customers. The data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data presentation, and conclusion drawing, supported by triangulation techniques to ensure data validity. The findings reveal that service responsiveness at the Sindang Service Branch has been procedurally institutionalized, particularly in the initial stages of service interaction. Customers generally receive prompt acknowledgment, and complaint recording mechanisms are systematically implemented through both offline and digital channels. However, responsiveness remains predominantly procedural rather than outcome-oriented. Timeliness emerges as the weakest dimension, especially in technically complex services such as pipeline repairs and new household connection installations. Constraints related to procedural rigidity, limited technical personnel, uneven staff competence, and insufficient integration between administrative and technical units hinder effective service resolution. The study concludes that while the Sindang Service Branch demonstrates commitment to responsive public service delivery at the procedural level, improving performance-based responsiveness requires strengthening service-level standards, enhancing human resource capacity, improving inter-unit coordination, and optimizing integrated information systems. These efforts are essential to improve service timeliness, customer satisfaction, and public trust in regional drinking water services. Keywords: Service responsiveness, public service quality, customer complaint handling, regional drinking water company, public administration